Implementasi Metode Praktik Langsung Dalam Pelatihan Desain Grafis pada Murid Paket B dan C di SKB Kota Serang - Nisrina Nur Aisyah; Ratu Amelda; Chanda Maulana Irawan; Siska Resti Maysara; Arlis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of Canva based graphic desain learning methods for Package B and C students at SKB Kota Serang and to evaluate its impact on digital skills, creativity and learning motivation. Using a qualitative descriptive approach with triangulation techniques, data were collected through observations, in depth interviews, and documentation. The findings indicate that the application of interactive and practice based learning, supported by tutor guidance, successfully enhances students digital literacy, design skills, and self confidence. Learners were able to produce visual works such as promotional posters and experienced learning that was more engaging, relevant, and beneficial for real world contexts such as entrepreneurship and social media. This study highlights the strategic role of non formal education in developing digital competencies and supporting creative economic empowerment in the digital era.